Racial disparities with PRN medication usage in inpatient psychiatric treatment - Areef S. Kassam; Peter Karalis; Taline Aydinian; Anita Panjwani; Gabriel Martinez; Aaron Whiteman; Magdoline Daas; E. Ann Cunningham (Schizophrenia, 2024)
Abstract Racial disparities in psychiatric diagnoses and treatment have significant public health implications, contributing to inequities in healthcare outcomes. We specifically examined racial disparities regarding pro re nata (PRN), or as needed, medications. Data from 14,616 encounters across 2019–2020 within Community Health Network’s inpatient psychiatric setting in Indianapolis, Indiana were included in this study. Due to the demographic sample size, analyses were narrowed to Black and White patients. Primary outcomes included comparisons across race for all PRN administrations and PRN administrations of antipsychotics vs. non-antipsychotics. Logistic regression was used to examine associations between race and PRN administrations by medication category, including all antipsychotics vs. non-antipsychotics overall, hydroxyzine, and lorazepam, independently. Significant differences in the percentage of administrations between Black and White patients were observed. Black patients received more PRN medications overall (71.0%) compared to White patients (67.7%) (p < 0.01). Further, while 17.7% of Black patients were administered PRN antipsychotics, this was true for only 8.2% of White patients (p < 0.001). When comparing antipsychotic PRNs with non-antipsychotic, hydroxyzine, and lorazepam PRNs, independently, Black patients were 58% (OR 1.58, p < 0.001), 109% (OR 2.09, p < 0.001), and 32% (OR 1.32, p < 0.001), more likely to receive antipsychotic PRNs, respectively, than White patients, controlling for sex, age, length of stay, and psychotic disorder diagnosis. Our study identifies yet another area of medical care with significant racial disparities. In this analysis of PRN medications during psychiatric admission, we identified significant differences in medication utilization by race. This information provides a basis for further investigation of disparities in patient-centered data.